Peak runoff reduction through the use of various detention tank systems - Neo, Nelson Zhi Shen (2015)
With the launch of the Active, Beautiful, Clean (ABC) Waters Programme, the Public Utilities Board (PUB) has encouraged developers and consultants to implement ABC features into the design of new developments or upgrading of existing sites. The latest Code of Practice published by the PUB on surface water drainage requires a development site greater than 0.2ha to control the peak runoff discharged from the site. This study investigates how the peak runoff reduction could be achieved through the implementation of detention tanks using two methodologies. The two methodologies proposed were an excel spreadsheet, and using the Storm Water Management Model (SWMM) software. Through comparison of the results of the two methodologies, it was concluded that using the excel spreadsheet was an effective preliminary analysis tool for detention tank sizing. SWMM software could be used as a secondary tool to further enhance the precision of the results. Future research could concentrate on the quality aspects of stormwater management, integrating with other ABC features and also on the economic analysis.